Toward an International Model of Islamic Boarding School: Foundational Philosophy, Curriculum Integration, and Educational Transformation - Sodikin, Sodikin (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The internationalization of pesantren (Islamic boarding schools) raises critical questions regarding the balance between global engagement and the preservation of Islamic epistemological and ethical foundations. This study examines how pesantren conceptualize and implement internationalization through curriculum integration and institutional transformation without adopting Western-centric educational models. Using a qualitative case study approach, data were collected through in-depth interviews with pesantren leaders and educators, complemented by curriculum and policy document analysis. The findings reveal that internationalization is framed as a civilizational project rooted in universal Islamic philosophy (al-‘ālamiyyah), classical Islamic cosmopolitanism, integrative epistemology, and moderation (wasathiyah). Pesantren adopt dialogic, interdisciplinary, and contextual curricula that synthesize turāṯ with contemporary academic methodologies, rejecting the dichotomy between religious and secular knowledge. Engagement with global academic networks selectively fosters governance reform, research culture, and knowledge exchange while preserving moral and scholarly authority. This study contributes theoretically by positioning pesantren internationalization as a normative-critical and holistic educational model capable of bridging Islamic values with global challenges.